2022
DOI: 10.3389/fimmu.2022.882972
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Associated Enhanced Disease and Pathogenic Human Coronaviruses

Abstract: Vaccine-associated enhanced disease (VAED) is a difficult phenomenon to define and can be confused with vaccine failure. Using studies on respiratory syncytial virus (RSV) vaccination and dengue virus infection, we highlight known and theoretical mechanisms of VAED, including antibody-dependent enhancement (ADE), antibody-enhanced disease (AED) and Th2-mediated pathology. We also critically review the literature surrounding this phenomenon in pathogenic human coronaviruses, including MERS-CoV, SARS-CoV-1 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 147 publications
3
36
0
1
Order By: Relevance
“…Thus, P&S induces similar systemic binding and neutralizing antibody levels—a correlate of protection in humans—and elicits mucosal IgA, IgG, CD4 + T RM cells, and CD8 + T RM cells. Only P&S elicits T H 1 and T H 17 CD4 + T RM cells and not pathogenic T H 2 cell responses, which have been associated with vaccine-associated enhanced disease (VAED) ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, P&S induces similar systemic binding and neutralizing antibody levels—a correlate of protection in humans—and elicits mucosal IgA, IgG, CD4 + T RM cells, and CD8 + T RM cells. Only P&S elicits T H 1 and T H 17 CD4 + T RM cells and not pathogenic T H 2 cell responses, which have been associated with vaccine-associated enhanced disease (VAED) ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…During the pandemic, the antibody-dependent enhancement (ADE) of infection is a possible critical factor, since the present strains are different from the original, with potentially unfavorable consequences (Yahi et al, 2021 ). Although ADE and antibody-enhanced disease (AED) are theoretically rare phenomena for genetic vaccines, they should be studied more extensively (Gartlan et al, 2022 ). Since vaccine-associated enhanced disease (VAED) was observed in the SARS-CoV-1 pandemic, the same trials to investigate VAED should be repeated for the current SARS-CoV-2 pandemic (Gartlan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although ADE and antibody-enhanced disease (AED) are theoretically rare phenomena for genetic vaccines, they should be studied more extensively (Gartlan et al, 2022 ). Since vaccine-associated enhanced disease (VAED) was observed in the SARS-CoV-1 pandemic, the same trials to investigate VAED should be repeated for the current SARS-CoV-2 pandemic (Gartlan et al, 2022 ). Additionally, the increased hospital and ICU admission rates in fully vaccinated patients are a cause for concern, as according to Munoz F.M.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the authors produced monoclonal antibodies against these immunodominant epitopes and showed, in vitro in Vero E6 cells, which lack FcRs, that antibodies against “protective” epitopes block viral entry, whereas two antibodies against the “pathogenic” epitopes elicited enhanced infection ( Wang et al, 2016 ). Nonetheless, the histopathological data published by Tseng et al (2012) ; Liu et al (2019) , and Wang et al (2016) have been criticized due to their poor quality, difficulties in interpretation, and the absence of a histopathological scoring system, which may have biased the interpretation (reviewed in Gartlan et al (2022) ). In contrast to previous results, although protective neutralizing immune responses were elicited ( Zhou et al, 2005 ), Luo et al showed that immunization of rhesus macaques with an inactivated SARS-CoV-1 vaccine led to protection rather than enhanced infection, even in the context of low levels of neutralizing antibodies ( Luo et al, 2018 ).…”
Section: Vaccines and Vaccine Candidates With Evidence Of Vaccine-ass...mentioning
confidence: 99%
“…These vaccine candidates and approved vaccines are based on different platforms and formulations, but most target the Spike protein (WHO, 2020;Covid-19 Vaccine, 2022). There were initial concerns about the possibility that the new SARS-Cov-2 vaccines may carry a risk of VAERD (Arvin et al, 2020;Halstead, 2021;Jamrozik et al, 2021a;Munoz et al, 2021;Gartlan et al, 2022), but two years of epidemiological data in clinical trials and widespread administration of these vaccines in the general population have made it possible to alleviate them. These concerns were based on several observations, a number of which are mentioned below:…”
Section: Have Sars-cov-2 Vaccines and Vaccine Candidates Shown Any Ri...mentioning
confidence: 99%